The relationship between coping strategies, alcohol expectancies, drinking motives and drinking behaviour - Hasking, Penelope; Lyvers, M.; Carlopio, C. (Pergamon, 2011)
Numerous models have been proposed in an attempt to explain both alcohol use and alcohol abuse. Many of these models propose that drinking behaviour is the result of a complex interplay of cognitive and behavioural variables including coping strategies, alcohol expectancies and motives for drinking. However few studies have explored how these elements may work together to predict drinking. The current study proposed a mediational model of alcohol use in which coping strategies are related to alcohol expectancies, which in turn are related to drinking motives. Drinking motives were then viewed as proximal predictors of drinking behaviour. There were 454 participants (55.78% female) who completed self-report questionnaires assessing the above constructs. Approximately half the participants completed the questionnaires online, while the others completed the paper and pencil versions of the same measures. Findings generally supported the hypothesised model. The relationship between avoidant coping and drinking behaviour was mediated by alcohol expectancies of increased confidence and tension reduction, which in turn were related to drinking motives. As expected, drinking motives were positively related to drinking behaviour. Negative expectancies were also directly related to drinking behaviour. The results are discussed in light of cognitive models of drinking, and implications for prevention and early intervention of alcohol-use problems.